[60]fullerene-containing thermotropic liquid crystals - Guillon, Daniel; Donnio, Bertrand; Deschenaux, Robert (: Wiley-VCH Verlag GmbH & Co. KGaA, 2012)
A review. [60]Fullerene-contg. liq. crystals have reached a high degree of sophistication from the point of view of both their structure and mesomorphic properties. Owing to their unique photophys. and electrochem. characteristics, [60]fullerene-based liq. crystals are promising compds. for the development of nanotechnol. by the bottom-up approach. Indeed, good studies have shown that liq.-cryst. fullerenes can play a major role in electron transport and photoconduction, and photoinduced electron and/or energy transfer has been achieved in donor-acceptor dyads when combined with ferrocene, tetrathiafulvalene, or oligophenylenevinylene. [on SciFinder(R)]
Keywords: review C60 fullerene thermotropic liq crystal